Microleakage of a Self-Adhesive Flowable Composite, a Self-Adhesive Fissure Sealant and a Conventional Fissure Sealant in Permanent Teeth with/without Saliva Contamination - Zohre Sadat Hosseinipour; Alireza Heidari; Mehdi shahrabi; Kiana Poorzandpoush (Tehran University of Medical Sciences, 2019)
Objectives: Application of fissure sealants is a practical method for prevention of occlusal pit and fissure caries. Microleakage is an important factor affecting the success of fissure sealant treatment. This study aimed to assess the microleakage of a self-adhesive flowable composite, a self-adhesive fissure sealant and a conventional fissure sealant in permanent teeth with/without saliva contamination. Materials and Methods: This in vitro, experimental study evaluated 108 extracted human third molars, which were randomly divided into six groups (n=18) of control, Denu-Seal conventional fissure sealant applied on etched enamel with/without saliva contamination, Vertise Flow self-adhesive flowable composite applied on rinsed and dried enamel with/without saliva contamination and Prevent Seal self-adhesive fissure sealant applied on rinsed and dried enamel with/without saliva contamination. Microleakage was assessed using the dye penetration technique and subsequent observation of samples under a stereomicroscope. Data were analyzed using the Kruskal-Wallis and Tukey's test. Results: Microleakage of the conventional fissure sealant with/without saliva contamination was significantly lower than that of other groups (P<0.05). Conclusion: Microleakage of the conventional fissure sealant is less than that of self-adhesive fissure sealant and self-adhesive composite, irrespective of saliva contamination.